A Qualitative Course-Based Exploration of the Spiritual Character of Child and Youth Care Practitioners - Wan, Andrea; Ganske, Ashlyn; Kucherepa, Brian; Seville, Deanna; Spornitz, Mianna; Gebre, Mekdes; Bellefeuille, Gerard (Eximia, 2022)
This paper presents the findings of a qualitative course-based study that explored how child and youth care (CYC) students draw on their spirituality in forming connections with children and youth. A nonprobability purposive sampling strategy was used to recruit CYC student participants in their second, third, and fourth years of study. Due to the ongoing COVID- 19 pandemic, data were collected using an online questionnaire and Zoom video conferencing focus groups. An inductive data analysis revealed three dominant themes: a) being respectful of the spiritual practices and beliefs of others; b) maintaining a sense of hope, meaning, and purpose as an important aspect of mental health; and c) creating, negotiating, and transcending boundaries without sacrificing one’s spiritual identity.